How do multiple deprivations in nuanced urban and rural settings affect health differently in South Africa? Evidence from NIDS data, 2017 - Josue Mbonigaba; Msawenkosi Dlamini (BMJ Open)
Introduction/objective Previous research on socioeconomic factors influencing health outcomes has often centred on the urban–rural divide, overlooking the nuanced variations within these categories. This study enhances our understanding by moving beyond traditional comparisons to examine the specific impacts of multiple deprivations on self-rated health across traditional authority areas, rural formal areas, urban informal areas and urban formal areas. By doing so, it captures the unique challenges and health implications associated with varying deprivation levels within these diverse contexts.Methods We first constructed the Provincial Index of Multiple Deprivation for each selected region using Wave 5 data from the National Income Dynamics Study, enabling an assessment of the health impacts of multiple deprivations across South Africa. During the estimation of the ordered probit model, collinearity issues emerged. To address this, we applied Principal Component Analysis (PCA) to create independent components which were then incorporated into the model. Self-reported health (SRH) was used as the dependent variable, allowing us to gain valuable insights into the relationship between health and multiple deprivation within these four contexts.Results The study uncovers significant disparities in deprivations, with the most deprived areas being rural formal areas and traditional authorities’ areas and the least deprived being the urban formal areas. The PCA variables in the ordered probit model suggest that traditional and rural formal areas soften the effect of multiple deprivations on SRH relative to urban areas. In contrast, informal urban areas enhance the negative effect of multiple deprivation SRH relative to urban formal areas.Conclusion/recommendations The interaction between multiple deprivation variables and the specific areas examined in this study reveals varying impacts on health. Greater attention should be given to finer geographical characteristics in residential contexts to ensure that interventions are tailored effectively to the specific needs of each area. This focus is particularly important, as the local context may significantly impact health—a fundamental component of life and well-being.